Development of Data Acquisition System on an Arduino-Based Tensile Test Machine for Composite Materials - Dede Lia Zariatin; Yani Kurniawan; N.A Reza Afika (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa dan Inovasi, 2023)
A tensile testing machine with a lower load capacity is needed to identify the mechanical properties of composite materials. Tensile testing machines for composite materials are available in the market but at high prices. Previously, using a pneumatic system, a tensile testing machine for composite materials with a maximum load of 2000N was developed. However, this tensile test machine still needs improvement because the display of eventuating forces is only in numbers, not yet including a test graph. Therefore, this study developed a prototype data acquisition system for a tensile test machine to record the test results in more detail, both numbers and graphs. This data acquisition system uses the Arduino Uno Microcontroller, which processes data from the load cell through the HX711 module intermediary. A tensile test was carried out using a bamboo fiber composite material to validate the results of testing the prototype of this data acquisition system. Furthermore, the test results data are compared with the results on the indicators of the existing tensile test machine. The test was carried out nine times with an average tensile force of 1.66 N/mm2, while the average tensile force on the tool indicator was 2.02 N/mm2. There is a difference in the average test results equal to 12%. This difference is a systematic error because nine experiments have shown the same trend, with standard error and standard deviation of 0.3368 and 0.1123, respectively. The systematic error is compensated through calibration between the load cell of the tensile test machine and a series of data acquisition systems based on Arduino Uno.